(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Madhya Pradesh enacted the Panchayat Raj Adhiniyam, 1993to establish the three level Panchayati Raj system in the State. It was thefirst state to hold elections after the 73rd amendment. In 2001, thePanchayati Raj Adhiniyam was amended by the Gram Swaraj Adhiniyam, whichbrought about significant changes in the structure of Panchayati Raj, bystrengthening Gram Sabhas and directly constituting committees at the GramSabha level to plan and implement programmes. Recently, the law has beenfurther amended to restore the position of the Gram Panchayat as the executivearm of self-government. It has been reported that Madhya Pradesh has decided toreplace the separate village-level committees for development, education,health, infrastructure, security, agriculture, public property and socialjustice with two new committees the Gram Nirman Samiti and Gram Vikas Samiti,both chaired by the Sarpanch. The mission of the different committees is holistic andaccelerates development of dense areas around a probable growth centre in azila Panchayat (or come together of neighboring Gram Panchayats) from side toside Public Private Partnership ("PPP") framework for providing urbanamenities and livelihood opportunities to get better the excellence of life inrural areas. The scheme aims to provide urban amenities and livelihoodopportunities in rural areas to overpass the rural urban divide.